Analysis of the autopsy, toxicological, and psychiatric reports of Portugal's first major forensic case: part III - Ricardo Jorge Dinis-Oliveira (Oxford University Press, 2021)
This work presents an odd historical record obtained through more than 14 years of research regarding one of the first major European forensic cases. The presumed homicide of Mário Guilherme Augusto de Sampaio in 1890 was allegedly perpetrated by his uncle, the prestigious doctor Vicente Urbino de Freitas. This famous poisoning had international repercussions for decades, with the participation of several forensic experts that made the history of forensic sciences, namely forensic toxicology and pathology. This third work aims to collect, restore, and analyse all the forensic evidence, particularly from the autopsy, toxicological, and psychiatric forensic reports. Facts regarding the life of Vicente Urbino de Freitas during his exile in Brazil were also recovered, along with a vast and outstanding assortment of forensic medicine photographs from the 19th century.